Investigation of the hydraulic conductivity of soils in an area of municipal solid waste landfill through field and laboratory tests - De Jesus, Lucas Scarpanti [UNESP]; Fernandes, Jeferson Brito [UNESP]; Giacheti, Heraldo Luiz [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2013)
A contaminant plume due to leachate infiltration was found in the solid waste landfill from Bauru, SP. The soil hydraulic conductivity (K) is an important parameter to understand the moving of this plume. This paper intends to show representative K values for the soils that occur in the vicinity of this landfill determined by field and laboratory tests. There are four soil types in the area: colluvium, alluvium, sandstone residual soil and the sandstone. Laboratory tests were performed using constant and variable head in rigid and flexible wall permeameters. Slug tests and hydraulic conductivity tests with the Guelph permeameter were also carried out in situ in the area. Representative K values of 3.7x10-7 m/s for the saturated zone and 2.4x10-8 m/s for the unsaturated zone were determined for the residual soil. A K value of 5.3x10-5 m/s was obtained for the colluvium soil. A great variation of K with depth was observed for the alluvium and the assumed average values for the saturated zone were 7.9x10-7 m/s and 1.1x10-4 m/s for the unsaturated surficial layer. An average K value of 3.3x10-8 m/s was determined in laboratory for the sandstone and it was assumed representative for this material.
Investigação da condutividade hidráulica dos solos de uma área de aterro de resíduos sólidos urbanos por meio de ensaios de campo e laboratório
Keywords: Geo-environmental investigation; Hydraulic conductivity; Solid waste landfill; Tropical soils